Gay Liberation Is One Thing, but Nobody Likes a Dyke: Emerging Frames in Queer Radio - (:unkn) unknown (My University, 2016)
This thesis examines how a social movement uses the media to progress in society. I conduct a framing analysis on the queer community’s use of radio during two time periods: 1970s queer radio program Gay Perspective and a 2015-2016 program, Queery. I examine the show through three emerging frames: Cultured, Diversity, and Assimilation. The thesis studies how segments of the LGBTQIA+ community framed the discussion of gay rights in the 1970s and how those frames have (and haven’t) changed in 2016. Gay Perspective focused much of its energy on trying to demonstrate the need for rights and attempts to demonstrate how the queer community’s members could be functioning members of mainstream society. By 2015-2016, at least some of those rights had been won, freeing queer-rights advocates to wrestle with definitional problems about membership within the community, something addressed in Queery. These findings show that social movements are constrained overall by the larger culture in which they are embedded, and call into question the use of radio as an effective tool for transforming a social movement’s status within society.
Keywords: Assimilation; Diversity; Framing; Queer; Radio; Sexuality